Analysis of Equity Disputes in Listed Companies With Dispersed Ownership Structure and Protection of Small and Medium Shareholders’ Interests - He, Chun Xi; Soh, Wei Ni; Ong, Tze San; Lau, Wei Theng; Zhong, Bin (Frontiers in Psychology, 2022)
This paper selected Vanke as the case to study the governance problems of Vanke and the protection of the interests of small and medium shareholders under the situation of equity disputes. At the same time, the study further explored the advantages and disadvantages of the dispersed ownership structure, the long-term impact on the company's development and the choice of the involved corporate governance methods under the current Chinese capital market conditions. This paper adopted the event research method and selected the period from June 2015 to June 2017 (24 months) as the observation period to analyze the market performance impact of Vanke in the equity disputes. At the same time, this paper also measured Vanke's individual stock rate of return (Rit) and market rate of return (Rmt), and calculated Vanke's normal rate of return (E(Ri,t)), abnormal rate of return (ARi,t) and cumulative abnormal rate of return (CARi) during different event windows ([-3,10]). Vanke's shareholding was too dispersed and the stock price had been sluggish for a long time, which had greatly reduced the acquisition difficulty and cost of Baoneng, thus triggering the "barbarian invasion" of Baoneng. In the struggle for control, whether it was Vanke's anti-takeover measures or China Resources, Baoneng and Evergrande's competition for equity, their actions had harmed the interests of small and medium shareholders. The market supervision department was too lenient to supervise and punish the interests of small and medium shareholders, and opportunism made behaviors that infringe on the interests of others more reckless. However, small and medium shareholders cannot actively participate in the company's management decision-making to safeguard their legitimate rights and interests, which intensifies the violations of all parties in the equity disputes, thus forming a vicious circle. Therefore, the protection of the interests of small and medium shareholders required the joint efforts and consciousness of regulators, small and medium shareholders and acquirers.